2011
DOI: 10.1097/aap.0b013e318228c835
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic Schwann Cell Toxicity Is Time and Concentration Dependent

Abstract: Background-Peripheral nerve blocks (PNB's) with local anesthetics (LA's) are commonly performed to provide surgical anesthesia or postoperative analgesia. Nerve injury resulting in persistent numbness or weakness is a potentially serious complication. LA's have previously been shown to damage neuronal and Schwann cells via several mechanisms. We sought to test the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 45 publications
1
66
1
6
Order By: Relevance
“…In this way, the use of high volumes of this class of drugs should be associated with dilution, i.e., being administered at lower concentrations than usual 15 to minimize the risks of intoxication. Additionally, it is possible that in the light of these lower concentrations, the effective blockade is related only to sensitive fibers in function of a more slender caliber in detriment the motor fibers, while still maintaining the analgesic quality 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the use of high volumes of this class of drugs should be associated with dilution, i.e., being administered at lower concentrations than usual 15 to minimize the risks of intoxication. Additionally, it is possible that in the light of these lower concentrations, the effective blockade is related only to sensitive fibers in function of a more slender caliber in detriment the motor fibers, while still maintaining the analgesic quality 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, laboratory studies have shown that intrathecal application of bupivacaine causes severe injuries in the sensory and motor system [6][7][8]. Although the mechanism lying behind is not known, bupivacaine-induced neurotoxicity has been proposed to be associated with neuronal apoptosis [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…O tempo de médio de latência, considerando todos os pacientes do estudo, foi de 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) minutos. Quando considerado apenas os pacientes que receberam bloqueios com a concentração de 0,25% (a concentração mais pró-xima da CME90), o tempo médio de latência foi de 20 (15)(16)(17)(18)(19)(20)(21)(22)15) minutos. Os tempos médios de latência para cada concentração analisada estão resumidos na tabela 4.…”
Section: Resultsunclassified